Synthesis and optimization of mesoporous silica nanoparticles for ruthenium polypyridyl drug delivery - Harun, Siti Norain; Ahmad, Haslina; Lim, Hong Ngee; Chia, Suet Lin; Gill, Martin R. (MDPI AG, 2021)
The ruthenium polypyridyl complex [Ru(dppz)2PIP]2+ (dppz: dipyridophenazine, PIP: (2-(phenyl)-imidazo[4,5-f ][1,10]phenanthroline), or Ru-PIP, is a potential anticancer drug that acts by inhibiting DNA replication. Due to the poor dissolution of Ru-PIP in aqueous media, a drug delivery agent would be a useful approach to overcome its limited bioavailability. Mesoporous silica nanoparticles (MSNs) were synthesized via a co-condensation method by using a phenanthrolinium salt with a 16 carbon length chain (Phen-C16) as the template. Optimization of the synthesis conditions by Box–Behnken design (BBD) generated MSNs with high surface area response at 833.9 m2g−1. Ru-PIP was effectively entrapped in MSNs at 18.84%. Drug release profile analysis showed that Ru-PIP is gradually released, with a cumulative release percentage of approximately 50% at 72 h. The release kinetic profile implied that Ru-PIP was released from MSN by diffusion. The in vitro cytotoxicity of Ru-PIP, both free and MSN-encapsulated, was studied in Hela, A549, and T24 cancer cell lines. While treatment of Ru-PIP alone is moderately cytotoxic, encapsulated Ru-PIP exerted significant cytotoxicity upon all the cell lines, with half maximal inhibitory concentration (IC50) values determined by MTT (([3-(4,5-dimethylthiazol-2-yl)-2,5-dephenyltetrazolium bromide]) assay at 48 h exposure substantially decreasing from >30 µM to <10 µM as a result of MSN encapsulation. The mechanistic potential of cytotoxicity on cell cycle distribution showed an increase in G1/S phase populations in all three cell lines. The findings indicate that MSN is an ideal drug delivery agent, as it is able to sustainably release Ru-PIP by diffusion in a prolonged treatment period.